Actualization of Religious Potential in Forest Ecosystems Protection - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2013)
Declared by the United Nations as the International Year of the Forest, 2011 demonstrated the signi#cance of forest ecosystems to all humans and the entire Earth. Religions had already become important allies in preventing damage to forests. Different religious traditions offer various proposals for forest conservation and afforestation. Since 1970 and especially after the jubilee year of 2000, people of faith established many ecological organizations to engage in environmental conservation because of their religious beliefs. All major religious traditions have a lot to offer. This article examines the way organized religions and faith-based ecological organizations are engaged in many environmental projects concerning forest ecosystems. It looks at the ecological activity of faith-based organizations such as the Chipko Movement, Appiko movement, Swadhyaya community, and the Ecological Movement of St. Francis of Assisi. The article shows that the actualization of religious potential in protecting forests is accomplished through active prevention of deforestation and climate change, afforestation, and the implementation of environmentally friendly technology.